Use of PCR to estimate the prevalence of Equus caballus papillomavirus in aural plaques in horses - Gorino, Ana Claudia [UNESP]; Oliveira-Filho, Jose P. [UNESP]; Taniwaki, Sueli A. [UNESP]; Basso, Roberta M. [UNESP]; Zakia, Luiza S. [UNESP]; Araujo, João P. [UNESP]; Borges, Alexandre Secorun [UNESP] (Elsevier, 2013)
Aural plaques occur on the skin of the medial surface of the pinnae of horses. In this study the presence of Equus caballus papillomavirus (EcPV)-3 and -4 DNA was assessed in 45 such plaques using a 'touchdown' PCR. Papillomaviruses (PVs) were detected in 62.3% (28/45) of samples: EcPV-3 and -4 DNA in 8.89% (4/45) and 37.78% (17/45) of samples, respectively, with 15.56% (7/45) of samples exhibiting co-infection. Viral DNA was not detected in 37.78% (17/45) of samples, suggesting the possible existence of other equine PVs. Neither EcPV-3 nor -4 were detected in negative control skin. This study is the first to evaluate the prevalence of these two viruses in equine aural plaques. © 2013 Elsevier Ltd.
Keywords: Aural plaques; Horse; Papillomavirus; PCR